150 years later: a look at Loschmidt's contributions to organic chemistry1. (13th February 2013) - Roth, Heinz D.
<x xml:space="preserve">Abstract</x> Examining the structures presented by Loschmidt in 1861 shows that he portrayed organic structures in a visually appealing way, but the structures do not support several claims and accolades of Loschmidt's modern‐day champions. There is serious doubt that Loschmidt viewed benzene as a planar cyclic array of six carbon atoms; he did not understand positional isomerism of benzene derivatives or the essence of geometric isomerism. He did not recognize that carbons of the C6 nucleus could only be singly bonded to a substituent. Concerning his "prediction" of cyclopropane, Loschmidt may have been the first to consider a "circular" array of three atoms; this achievement must be viewed in the light of similar predictions for a cyclic dinitrogen oxide, tetracyclohexane, heptacyclononane, and a [1, 1]‐metacyclophane. His structures worked well for strings of sp2‐hybridized carbons or for molecules with chains of tri‐substituted carbons. Loschmidt did not differentiate between the bond lengths of double and triple bonds, as claimed. Copyright © 2013 John Wiley & Sons, Ltd.